2019
DOI: 10.1139/cjm-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and degradation of polyhydroxyalkanoates by lipase-producing bacteria

Abstract: Biodegradation of short chain length polyhydroxyalkanoates (scl-PHAs) and medium chain length polyhydroxyalkanoates (mcl-PHAs) was studied using two bacteria, Pseudomonas chlororaphis and Acinetobacter lwoffii, which secrete an enzyme, or enzymes, with lipase activity. These bacteria produced clear zones of depolmerization on petri plates containing colloidal solutions of PHA polymers with different monomer compositions. Lipase activity in these bacteria was measured using p-nitrophenyl octanoate as a substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Of these, three encode for intracellular lipases (EY04_08410, EY04_09635, EY04_02420), three encode a signal peptide and are extracellular lipases (EY04_21540, EY04_17885, EY04_32435), and one encodes for an intracellular PHA depolymerase (EY04_01535). In our previous study, the hydrolysis of the ester bonds of p-nitrophenyl-fatty acid substrates, and the ester bonds of PHA polymers of various subunit composition by the extracellular esterases/lipases was recorded in the culture media in which P. chlororaphis PA23 and A. lwoffii were grown ( Sharma et al, 2019 ). In the present study, two genes encoding intracellular lipases were cloned and expressed in E. coli BL21(DE3) to compare the properties and investigate its biodegradability in comparison with various biodegradable polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three encode for intracellular lipases (EY04_08410, EY04_09635, EY04_02420), three encode a signal peptide and are extracellular lipases (EY04_21540, EY04_17885, EY04_32435), and one encodes for an intracellular PHA depolymerase (EY04_01535). In our previous study, the hydrolysis of the ester bonds of p-nitrophenyl-fatty acid substrates, and the ester bonds of PHA polymers of various subunit composition by the extracellular esterases/lipases was recorded in the culture media in which P. chlororaphis PA23 and A. lwoffii were grown ( Sharma et al, 2019 ). In the present study, two genes encoding intracellular lipases were cloned and expressed in E. coli BL21(DE3) to compare the properties and investigate its biodegradability in comparison with various biodegradable polymers.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous report from this lab( Sharma et al, 2019 ), the cell free culture supernatant of Pseudomonas chlororaphis PA23 was shown to hydrolyze the ester bonds of p-nitrophenyl fatty acid substrates and PHA polymers with different subunit composition. In the present study, two genes encoding intracellular lipases from P. chlororaphis PA23 were cloned and expressed in E. coli BL21(DE3) to study the enzyme properties and investigate their degradation activity toward various biodegradable polymers such as small chain length (scl-) and mcl-PHAs, polylactic acid (PLA), polyethylene succinate (PES), and PCL.…”
Section: Introductionmentioning
confidence: 95%
“…Nitrosomonas have been proposed as a PHA-producing bacterium (Yang et al 2013). Previous reports have suggested that many bacteria, including denitrifiers, produce lipases rather than polymerases to degrade PHAs, though the reason is not known (Chu and Wang 2017, Jaeger et al 1995, Muhammadi et al 2015, Sharma et al 2019, Wang and Chu 2016. We hypothesized that either anaerobic condition or the presence of PHA or other bacteria might induce the lipase expression.…”
Section: Which Are the Lipolytic Mags And Why They Have Lipases?mentioning
confidence: 92%
“…Nitrosomonas have been proposed as a PHA-producing bacterium (Yang et al, 2013). Previous reports have suggested that many bacteria, including denitrifiers, produce lipases rather than polymerases to degrade PHAs, though the reason is not known (Chu and Wang, 2017;Jaeger et al, 1995;Muhammadi et al, 2015;Sharma et al, 2019;Wang and Chu, 2016). We hypothesized that either anaerobic condition or the presence of PHA or other bacteria might induce the lipase expression.…”
Section: Which Are the Lipolytic Mags And Why They Have Lipases?mentioning
confidence: 95%